Social policy of modern Kazakhstan: problems and prospects - Spanova, B.K.; Romanko, E.B.; Musabekova, А.О.; Huszti, Zs. (BUKETOV BUSINESS REVIEW, 2019)
The current state of social policy in Kazakhstan was studied. The purpose, objectives and definitions of social policy in the broad and narrow sense of the word are shown, the structure of social policy is reflected. The basic principles of social policy are substantiated. The instruments of state social policy are considered. The assessment of directions and functions of social policy, the main purpose of social policy, conditions of transition of the Republic of Kazakhstan to the social state, the role of the State budget is given. National Fund, in the social sphere of the state. It is noted that in the next decade in the activities of the state priority are five key areas, the Republic of Kazakhstan is at the second stage of transition to a socially oriented market economy. The implementation of tasks on the basis of the Address of the First President of the Republic of Kazakhstan «growth of well-being of Kazakhstanis: increase of income and quality of life» is analyzed. The key indicators of social sphere provision, criteria of targeted social assistance: social measures of the First President under the program «Aleumettik kamkorlyk» are presented. The renewal of social policy will contribute to improving the quality of life of the population; social policy is an interdependent process: the state creates conditions for social wellbeing. It is proved that Kazakhstan needs an updated social policy, in this regard, the Government should establish clear and transparent procedures for providing support to those who really need, organize control over the distribution, and the planned introduction of social cards of citizens can help this. All this should be facilitated by common approaches to the guaranteed volume of social support for citizens regardless of the region of residence. It is indicated that the head of state instructed the Government to develop common approaches, strengthen measures to strengthen social support of citizens and the availability of housing for socially vulnerable segments of the population. It is concluded that the social policy of the state can be effective only if it is aimed at creating jobs and involving the working-age population in the country's economy. It is necessary to solve the main tasks: — to create an effective model of social and labor relations; — to develop the social initiative of citizens; — to create an effective state system of management of social processes in Kazakhstan.